2014
DOI: 10.1179/1743294414y.0000000253
|View full text |Cite
|
Sign up to set email alerts
|

Which powders for cold spray?

Abstract: Since the major technological issues in cold spray are now controlled, the key parameter for successful coating relates to the powder. The influence of the main characteristics of the starting powder on the final coating properties remains rather unknown. This includes primarily metallurgical, morphological and physico-chemical characteristics of the particles. This article focuses on the so-called local approach to these characteristics to show that the current global approach is insufficient. The discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…It is clear that both answers depend on the powder shape, which influences the particle deformation at the impact and adhesion mechanisms. The resistance on tensile testing and the hardness of Ag irregular powder CGS sprayed coatings were higher than the Ag spherical shape, even after heat treatment [17]. Some mechanisms collaborate to the adhesion of the particles to the substrate as listed by Sun et al [18]: the adiabatic shear instability (ASI), caused by the high velocity of the powder particle, breaks the natural oxide film on the surface of both the particle and the substrate and the progressive plastic flow of the materials enables metallic bonding at atomic scale through direct contact between the adjacent fresh metal surfaces; mechanical interlocking, interfacial mixing, local melting and diffusion [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is clear that both answers depend on the powder shape, which influences the particle deformation at the impact and adhesion mechanisms. The resistance on tensile testing and the hardness of Ag irregular powder CGS sprayed coatings were higher than the Ag spherical shape, even after heat treatment [17]. Some mechanisms collaborate to the adhesion of the particles to the substrate as listed by Sun et al [18]: the adiabatic shear instability (ASI), caused by the high velocity of the powder particle, breaks the natural oxide film on the surface of both the particle and the substrate and the progressive plastic flow of the materials enables metallic bonding at atomic scale through direct contact between the adjacent fresh metal surfaces; mechanical interlocking, interfacial mixing, local melting and diffusion [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 88%
“…For example, the gas atomization process produces spherical powders, while the water atomization confers to the powders 2 of 18 an irregular shape, and it is typically a cheaper process than gas atomization [15,16]. About the selection of an specific shape powders to be used in CGS, for Jeandin et al [17], it depends on the answering of two main questions: first, how the particles impinge during the process and second, the nature of the bonding between two adjacent splats. It is clear that both answers depend on the powder shape, which influences the particle deformation at the impact and adhesion mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these techniques, cold-spray (CS) deposition provides intriguing advantages when spraying metallic particles on polymeric or FRPs substrates [9]: the deposition is made possible only by a mechanical interlocking mechanism, and no chemical reactions are required [10]. Moreover, compared with thermal spray processes, a less heat input is required in cold spray, therefore, the heat effects such as surface distortion, oxides, void, phase transformation, and residual stresses are considerably reduced in the coatings [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The cold spray coating deposition technique is a relatively new member of the thermal spray family but with the added advantage that coating particles remained in the solid state in the as-sprayed coating [1][2][3][4][5][6][7][8][9][10][11][12]. This property of the cold spray process prompted the authors to develop and study the new coating-substrate system by this process for different applications, especially for corrosive environments at temperatures near to 900 C. The study related to the cold spray process is reported in detail in the earlier publications of the authors [8,9].…”
Section: Introductionmentioning
confidence: 99%